Teaching integrated science through the use of interactive worksheets - Maharaj-Sharma, Rawatee (School of Education, UWI, St. Augustine, 2014)
In this work, interactive worksheets were used to teach a unit of integrated science to a group of 32 lower secondary school science students in Trinidad and Tobago. Observational checklists, students' journals, and perception opinionnaires were used to: (1) explore what effect interactive worksheets had on students' levels of participation during classroom learning, and (2) solicit students' views about the effectiveness of interactive worksheets to teach science. The findings revealed high levels of student participation and an overall expression of enjoyment among students when science was presented to them via this method. Students indicated that the experience was a meaningful one to them and suggested that interactive worksheets were effective in facilitating their understandings of the science content that was taught in the unit.
Keywords: Integrated science; Science education; Teaching methods; Secondary school students; Lower secondary education; Interactive learning; Worksheets; Trinidad and Tobago